Pyeongchang Winter Olympics – What’s Behind the Korean Unification Flag? - Ho, Shawn (2018)
The Korean unification flag, in its first version, consists of a blue and undivided Korean peninsula as well as Jeju island to its south. There is a lot more to this flag than meets the eye.